Evaluation of a commercial multiplex real-time PCR panel for identification environmental water antibiotic-resistant bacteria in hemoculture bottles - Thongdee, Pimwan; Narongdej, Putt; Wongthai, Passara; Nitchaphanit, Sirachat; Chuenchom, Kasidach; Krataipech, Kanlaya; Raksatham, Jantima; Peerapongpaisarn, Dutsadee; Oransathit, Wilawan; Ruekit, Sirigade; Ruamsap, Nattaya; Lertsethtakarn, Paphavee; et al. (My University, 2025)
Background: Antimicrobial resistance (AMR) is a major public health problem worldwide, and it is increasing, especially in developed and developing countries, including Thailand. Sepsis is a crisis and emergency causing the death of patients with a high mortality rate of 1 in 5 of the global population. Using inappropriate antimicrobial drugs to treat infections increases the chance of drug resistance in the microorganisms, and precise and rapid treatment is essential for patient management. Objective: This cooperative study aims to evaluate a commercial multiplex real-time PCR panel, QIAstat-Dx BCID GN Plus AMR Panel, to detect antimicrobial-resistant genes in the bloodstream. Materials and methods: Thirty bacterial samples were used to simulate bloodstream infections. The comparison between the QIAstat-Dx BCID GN Plus AMR Panel and the conventional PCR method was revealed. Results: Both methods gave concordant results for 12 samples, while results for 15 were discordant. Three samples could not be detected using the QIAstat-Dx BCID GN Plus AMR Panel because ebc gene is not included. The QIAstat-Dx BCID GN Plus AMR Panel revealed a sensitivity, specificity, positive predictive value, and negative predictive value of 91.50%, 93.30%, 74.10%, and 98.50%, respectively. Conclusion: The study indicated that the QIAstat-Dx BCID GN Plus AMR Panel Cartridge can detect common antimicrobial-resistant genes from the bloodstream. However, additional resistant genes should be included in the panel to cover various highly prevalent antimicrobial-resistant genes based on geographical location.
Keywords: Antimicrobial resistance; bacterial resistance genes; bloodstream infections; multiplex real-time PCR panel; QIAstat-Dx BCID GN plus AMR panel